Asymmetric Morphological Priming Among Inflected and Derived Verbs and Nouns in Greek - Loui, Sofia; Protopapas, Athanassios; Orfanidou, Eleni (Frontiers in Psychology, 2021)
The present study examined differences between inflectional and derivational morphology using Greek nouns and verbs with masked priming (with both short and long stimulus onset asynchrony) and long-term priming. A lexical decision task to inflected noun and verb targets was used to test whether their processing is differentially facilitated by prior presentation of their stem in words of the same grammatical class (inflectional morphology) or of a different grammatical class (derivational morphology). Differences in semantics, syntactic information, and morphological complexity between inflected and derived word pairs (both nouns and verbs) were minimized by unusually tight control of stimuli as permitted by Greek morphology. Results showed that morphological relations affected processing of morphologically complex Greek words (nouns and verbs) across prime durations (50-250 ms) as well as when items intervened between primes and targets. In two of the four experiments (Experiments 1 and 3), inflectionally related primes produced significantly greater effects than derivationally related primes suggesting differences in processing inflectional versus derivational morphological relations, which may disappear when processing is less dependent on semantic effects (Experiment 4). Priming effects differed for verb vs noun targets with long SOA priming (Experiment 3), consistent with processing differences between complex words of different grammatical class (nouns and verbs) when semantic effects are maximized. Taken together, results demonstrate that inflectional and derivational relations differentially affect processing complex words of different grammatical class (nouns and verbs). This finding indicates that distinctions of grammatical class are not of the same kind as distinctions of morphological relation (inflectional vs. derivational). Asymmetric differences among inflected and derived verbs and nouns seem to depend on semantic effects or/and processing demands modulating priming effects very early in lexical processing of morphologically complex written words, consistent with models of lexical processing positing early access to morphological structure and early influence of semantics.